Barite from the Upper Idrijca River valley (W Slovenia) - Jože Čar; Meta Dobnikar; Dragomir Skaberne (Geologija, 2002)
The Carnian – Julian beds exposed at the Tratnik landslide location in the Upper Idrijca River valley are of various lithology. Mudstones, shales and fine-grained sandtones prevail, containing lenses of micritic limestone and quartz conglomerate. Red coloured barite-quartz concretions, some of them septarias, and barite veins filled with light gray fibrous barite crystals were found in the fine-grained clastic rocks. Concretions with radial arrangementof barite crystals are of early diagenetic origin. Antitaxial barite veins found only in apical parts of folds near the thrust fault were formed in late diagenesis. Barite is replaced to great extent by younger, late diagenetic quartz, especially in the barite concretions.